Evaluation of an implementation strategy for a World Health Organization (WHO) public health report: The implementation of the International Perspectives on Spinal Cord Injury (IPSCI) in Romania - Groote, Per M. von; Skempes, Dimitrios; Bickenbach, Jerome E. (South Eastern European Journal of Public Health (SEEJPH), 2017)
Aim: This paper aims to evaluate a strategy for the implementation of public health policy recommendations from the World Health Organization’s (WHO) report “International Perspectives on Spinal Cord Injury” in Romania. More specifically, it seeks to: a) evaluate implementation actions with a focus on a number of people reached and status of completion at 12 months follow-up; b) describe implementation activities undertaken in the course of one year, and; c) evaluate perceived barriers and facilitators of implementation at 12 months follow-up. Methods: A cross-sectional design was adopted with two surveys administered in 2014/15 among key implementers in Romania. The questionnaires contained open-ended, multiple choice and 5-point Likert scale questions. Results on the implementation status, implementation activities performed and self-reported barriers and facilitators were analysed and reported using descriptive statistics. Results: Implementation completion rate was 75%, with 4390 persons directly or indirectly benefiting from the implementation-related activities listed in the final implementation plan reporting. A broad range of implementation experiences was reported. Most common activity types were delivery of services, technical trainings, implementation coordination and development meetings. Most useful tools and processes were the Romanian language version summary of the report, educational meetings, and local consensuses processes. Reported outcomes included the direct output produced, evidence of services provided, and individual or organizational level impact. Most barriers were named for the policymakers and academia as stakeholder groups and most facilitating influences for the private sector, with dependence of policymakers on constituency interest scoring highest barrier and the general availability of European Commission and European Structural Funds highest facilitator. Conclusion: The surveys proved to be both feasible and useful tools to expand our understanding of implementation and to supplement the more standard used implementation strategies at country level.